Contemporary challenges for specialist nursing in interstitial lung disease. Issue 1 (March 2018) - Russell, Anne Marie; Olive, Sandra; Lines, Sarah; Murphy, Anna; Hocking, Julie; Newell, Karen; Morris, Helen; Harris, Emma; Dixon, Catherine; Agnew, Sarah; Burge, Geraldine
The role of clinical nurse specialists (CNSs) in interstitial lung disease (ILD) is evolving in response to clinical guidelines and the growth of clinical research. The role is well established in the UK, although more ILD posts are needed to ensure supply meets clinical demand. This phenomenon is also happening across Europe. An appreciation of the similarities and differences between CNS and advanced nurse practitioners is important given the challenges in defining, developing and supporting this nursing specialisation. Globally, different models exist. In some countries charitable organisations take a leading role in supporting patients. Many European centres look to the National Institute for Health and Care Excellence guidelines and quality standards as a template to develop and evaluate the role of the ILD CNS. We present a UK perspective in the context of a government subsidised healthcare system to promote professional discussion and debate regarding the future of nursing practice in the ILD specialty. Key points: ILDs are often complex and associated with significant mortality, morbidity and co-morbid conditions that require a technical healthcare skill set There is worldwide shortage of nurses, low retention rates and retirement of many skilled nurses Collaboration across the ILD interdisciplinary community is needed to safeguard the future of our professions and high-quality patient care The ILD interdisciplinary and nurse network has identified key priorities to help secure the future of the ILD clinical and academic nurse specialism Educational aims: To explain the similarities and differences between clinical nurse specialists (CNSs) and advanced nurse practitioners (ANPs) in the context of ILD specialism To review contemporary nursing specialism in the UK's government subsidised healthcare system To stimulate discussion and debate across the European/international respiratory community regarding the clinical and academic development of the ILD CNS To identify key priorities that will support collaboration across the ILD interdisciplinary workforce in clinical practice and research Specialist nurses and interdisciplinary healthcare professionals are fundamental to the care of patients diagnosed with ILD. ILD specific clinical and academic standards are needed to sustain and develop a dedicated ILD workforce http://ow.ly/toee30h1UkW